As mulheres quilombolas na Paraíba: terra, trabalho e território - Monteiro, Karoline dos Santos (2013)
This dissertation aimed to unravel and/or understand the importance of women in social reproduction in maroon communities in which they live and their form of participation and integration in continuous production process of Paraiba agrarian space. We start from the observation that the lack or scarcity of information on the asymmetric gender differences in research in geography is a limit on the understanding of the processes and social relations that fall and form the agrarian landscape. It is with this concern that we launched in doing research on women in seventeen maroon communities located in three regions paraibanas: the Zona da Mata Paraibana, the Agreste Paraibano and Borborema. We propose to understand who are the Maroons women in these regions and what is their relationship with the land and territories that they occupy from: a) sexual division of labor in the communities in which they live, b) different forms of access to land and the many ways the right to this land is denied, and c) the forms of organization, participation and struggle of these women by maroons territories in Paraíba. We are concerned, therefore, with this research contribute to the understanding of Paraiba agrarian space from a subject who produces and stars in, however, is omitted in the geographical readings. We want this debate assist us in understanding who this maroon currently working woman in the state of Paraíba.